Nerve Growth Factor: Early Studies and Recent Clinical Trials - Rocco, Maria L.; Soligo, Marzia; Manni, Luigi; Aloe, Luigi (Current Neuropharmacology, 2018)
Since its discovery, nerve growth factor (NGF) has long occupied a critical role in developmental and adult neurobiology for its many important regulatory functions on the survival, growth and differentiation of nerve cells in the peripheral and central nervous system. NGF is the first discovered member of a family of neurotrophic factors, collectively indicated as neurotrophins, (which include brain-derived neurotrophic factor, neurotrophin-3 and neurotrophin 4/5). NGF was discovered for its action on the survival and differentiation of selected populations of peripheral neurons. Since then, an enormous number of basic and human studies were undertaken to explore the role of purified NGF to prevent the death of NGF-receptive cells. These studies revealed that NGF possesses important therapeutic properties, after topical administration, on human cutaneous pressure ulcer, corneal ulcers, glaucoma, retinal maculopathy, Retinitis Pigmentosa and in pediatric optic gliomas and brain traumas. The aim of this review is to present our previous, recent and ongoing clinical studies on the therapeutic properties of NGF.
Keywords: cancer cells